New Directions in the Historiography of Psychiatry. (14th December 2018) - Doroshow, Deborah; Gambino, Matthew; Raz, Mical
Abstract: Gerald Grob's work in the history of psychiatry over the course of almost fifty years created a model for how historians might successfully situate mental health in its social and political context, and how inseparable it was from this context. Over the last twenty years, the field has grown tremendously. Historians have incorporated categories of analysis like gender and race, methodologies like cultural history and intellectual history, and sought to continue Grob's quest to understand American mental health history as a critical component of American history writ large. In this piece, we suggest several potential areas for future study. Building on Grob's work on the asylum, we focus on the continued need to explore the texture of lived experience for both practitioners and those experiencing mental illness, both within and beyond the institution. In an era when the politics of deinstitutionalization continue to shape the modern mental health enterprise, we suggest that further examination of the consequences of deinstitutionalization is both inherently rich and relevant to contemporary mental health practice. Finally, we discuss opportunities for historians to engage with policymaking and social justice, pointing to incarceration and juvenile justice as two especially relevant areas for further study.